Industrial life cycle: relevance of national markets in the development of new industries for energy technologies – the case of wind energy - Marlene O'Sullivan (Journal of Evolutionary Economics, 2020)
About 20~years ago Klepper (1997) has shown that the life cycle theory, initially introduced for products, can also be applied to the development of industries. The industries that were examined to establish this theory were marked by relatively stable market conditions that are typically driven by innovation. However, research on the transition of the energy system has shown that markets for new energy technologies are driven by political support. As yet an analysis of the industry life cycle of an industry which has developed under politically driven market conditions has not been conducted. Therefore this paper examines the development of the global wind energy industry and the relevance of national markets in a globalized world. The study is founded on a large empirical database. A comparative analysis of various international and national developments was conducted using descriptive statistical methods. The findings show that the global development derives from the sum of individual national developments. It reveals a strong influence of national markets on the development of their respective wind energy industry. Therefore these findings provide relevant insides for the political debate on market support mechanisms in wind energy.
Keywords: O33; O57; 330; Industry life cycle; Wind energy industry; Relevance of national markets; Market development; Political support instruments; Market concentration